Solution of a contact problem for the prestressed layer and two coaxial elastic punches with initial (residual) stresses - Maksymchuk, D.N. (Reports of the National Academy of Sciences of Ukraine, 2015)
The article deals with the coaxial type problem of pressure of two cylindrical coaxial punches with residual stresses upon a layer with residual stresses within the framework of a linearized theory of elasticity. The research is carried out for the theory of finite deformations and two variants of the theory of small initial deformations with the elastic potential having arbitrary form.